(untitled) (Journal of Atomic and Molecular Sciences, 2021)
Ultrafast photodissociation dynamics of n-butyl iodide in the A-band has been studied by femtosecond time-resolved mass spectroscopy coupled with ion imaging. The time constant of n-C_4H_9I in the A-band with one photon excitation at 267 nm is measured to be (58±6) fs. The ion images of I (^2P_3/2) and I^* (^2P_1/2) at 267 nm and 274 nm are obtained and analyzed to yield corresponding speed and angular distributions. The dependences of dissociation mechanism on excitation wavelength and the size of the alkyl radical are discussed.